2005
DOI: 10.1111/j.1365-2834.2004.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses perception of work satisfaction at a Tertiary Care University Hospital

Abstract: Hospitals are facing serious challenges to provide high quality care with current nursing shortages. Nursing shortages are of major concern for Nursing Management, clinicians and administrators as they lead to impact on quality of care. Under-stressed, frustrated and demoralized nurses give rise to concern for hospital Nursing Management in providing quality care according to set standards. A descriptive qualitative research design was used to explore the registered nurses' perceptions regarding the high turno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 8 publications
4
75
0
11
Order By: Relevance
“…Thus, the finding suggests that improvement in recognition would logically lead to higher improvement in staff motivation. This finding is consistent with a study on health workers by Khowaja et al (2005) where recognition, appreciation on good performance and respect from their managers and colleagues were considered as critical factors of staff motivation. = 0-2.5 = low; X = 2.51-3.50 = average; X = 3.51 & above = high Responses from the study revealed that the staff of the banks in the metropolis perceive their level of role clarity to be high with a mean of 4.44 (Table 1).…”
Section: Resultssupporting
confidence: 82%
“…Thus, the finding suggests that improvement in recognition would logically lead to higher improvement in staff motivation. This finding is consistent with a study on health workers by Khowaja et al (2005) where recognition, appreciation on good performance and respect from their managers and colleagues were considered as critical factors of staff motivation. = 0-2.5 = low; X = 2.51-3.50 = average; X = 3.51 & above = high Responses from the study revealed that the staff of the banks in the metropolis perceive their level of role clarity to be high with a mean of 4.44 (Table 1).…”
Section: Resultssupporting
confidence: 82%
“…Moreover, job satisfaction is a key player in the study of human behavior at work and is treated as a critical challenge for management because of its effect on employee turnover and absenteeism (Abbas et al, 2014;Hartmann et al, 2014;Khowaja et al, 2005;Miller, Rutherford, and Kolodinsky's, 2008), procedural justice and on job training (Halepota and Shah, 2011;Shah, 2011) and intention to stay, organizational commitment and trust (Schreurs et al, 2015;Sourdif, 2004;Top et al, 2015;). Researchers reveal that employee job satisfaction relates to how individuals think and feel about their jobs (Alegre et al, 2016;Oliver, 1990;Randall et al, 1999;Spector, 1997) because it can impact on quality of life and overall happiness (Frey and Stutzer, 2010).…”
Section: Insert Table 1 Herementioning
confidence: 99%
“…5 Job satisfaction can be predicted by the variables as; type of the hospitals; private or public, autonomy, adequate staffing and work load, organizational support. [10][11][12][13] Researchers also having a say in job involvement, justice, and job stress, and organization commitment and economic cost commitment, and fairness in evaluation system. 8,14,15 Demographic factors are unique to each individual, such as age, gender, marital status, work experience, appear to affects nurses" work satisfaction and turnover intentions.…”
Section: Introductionmentioning
confidence: 99%